THE IMPORTANCE OF PRACTICAL TRAINING IN TEACHING PHYSICS - Soyipov Jasurali Japaraliyevich (Zeta Repository, 2023)
This article shows the methods of developing students’ interest in physics, the organization of independent learning in practical classes. In addition, aspects of the use of questions related to the assessment of classes in the classroom and in extracurricular activities in academic lyceums and secondary schools taught through advanced physics training are shown.